PENGARUH PENDIDIKAN, PELATIHAN DAN PENILAIAN PRESTASI KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN - Samsul Rizal; Isal Anwar Hasan; Irwan Abdullah; Anismayanti Anismayanti (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
This study aims to determine whether Education, Training and Job Performance Assessments affect PT. Suraco Jaya Abadi Motor Sentral Yamaha Makassar. The type of research used in this study is descriptive quantitative. Data processed is the result of distributing questionnaires to employees of PT. Suraco Jaya Abadi Motorbike Central Yamaha Makassar with a population of 40 employees and 36 respondents. The sampling method in this study uses Slovin formula, The data analysis technique used in this study is multiple linear regression, validity test and reliability test, hypothesis testing (T test and F test) and the coefficient of determination R. Based on the results of research and discussion It has been done that the results of this study show that there is a significant influence between education and training on improving employee performance and work performance assessment does not affect the improvement of employee performance.